Role of Maternal Reflective Ability for Substance Abusing Mothers - Pajulo, Marjukka (2008)
This paper reports on a study designed to explore factors contributing to better outcomes for substance abusing pregnant and parenting women in residential treatment, and, as a result, contribute to better outcomes for their children. The setting was three live-in units focusing in supporting both abstinence from substances and mother-child relationship. Participants were 18 mother-baby pairs in treatment from perinatal phase to 4 months of child’s age. Pilot results demonstrated more sensitive maternal interaction tended to be associated with higher pre-and postnatal reflective functioning and better child developmental scores at 4 months of child’s age. Reflective functioning (RF) refers to the essential human capacity to understand behavior in light of underlying mental states and intentions. An indicated conclusion is that enhancement of maternal reflective ability seems an important focus in developing the content and effectiveness of interventions for substance abusing mothers.